Deformation Analysis and Soil–Structure Interaction of Rigid Pavement Using the Finite Element Method (PLAXIS 3D) on the Feeder Access Road in the Nusantara Capital City Area - Eswan Eswan; Achmad Taufik; Achmad Munajir; Adelia Farahdita Maharani; Andri Fathian Noor (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The empirical approach to rigid pavement design does not fully capture the actual interaction between the concrete slab and its supporting soil layers, even though this aspect determines the long-term performance of the Nusantara Capital City (IKN) feeder access roads that serve heavy vehicles. This study aims to analyze the deformation and soil–structure interaction of rigid pavement using the finite element method through PLAXIS 3D software. The pavement system was modeled as three layers: the subgrade and lean concrete working floor using the Mohr-Coulomb constitutive model, and the concrete slab using elastic plate elements. Material parameters were derived from N-SPT test results and standard empirical correlations. Loading was modeled as four concentrated loads of 53.936 kN/m² representing the four wheels of a truck with a total load of 22 tons, and was simulated through staged construction. The analysis showed a maximum total displacement at the observed node of 0.01776 m (17.76 mm), which remains within the safe limit against deformation failure. These results confirm that the slab thickness designed using the empirical approach is capable of accommodating the vertical deformation caused by heavy vehicle loads, indicating that the numerical and empirical approaches are mutually complementary in ensuring design reliability.